Fundamentals of social work research - Engel, Rafael J (SAGE, 2010)
Rev. ed. of: The practice of research in social work. 2nd ed. c2009.; Includes bibliographical references and index.; This book is introduces research methods as an integrated set of techniques to investigate social issues and concerns common to social work practice. This textbook succinctly and clearly connects research methods to evidence-based practice enabling students to develop skills to critically evaluate research literature and provides the foundation for students interested in practice evaluation and research. The text encourages students to integrate issues of diversity and ethics as integral into their thinking as the plan and evaluate social work research.; CX080 Phương pháp nghiên cứu khoa học; DC068 Phương pháp nghiên cứu khoa học 1; DC070 Phương pháp nghiên cứu khoa học 2; CX406 Phương pháp nghiên cứu trong công tác xã hội